PENGARUH ONLINE CUSTOMER REVIEW DAN BEAUTY INFLUENCER TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH PADA APLIKASI TIKTOK DI SURABAYA - Putri, Ardiyanti Sanggie; Widyanti, Firlynisa Wafiyyah; Nabilla, Karunia Gadys; Kusmayati, Nindya Kartika (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This research aims to determine the effect of online customer reviews and beauty influencers on purchasing decisions for Wardah products on the TikTok App in Surabaya. Using a quantitative approach with purposive sampling, data were collected from 69 respondents and analyzed through multiple linear regression in SPSS software ver. 29. The regression equation is Y = 3,295 + 0,530X₁ + 0,232X₂. Simultaneously, both variables significantly influence purchasing decisions (F = 26,820; p < 0,05). Partially, online customer reviews have a significant positive effect (t = 4,967; p < 0,001), while beauty influencers show a positive but statistically insignificant effect (t = 1,989; p = 0,051). The suggestion in this study is that the Wardah brand continues to encourage an increase in positive customer reviews and maintain cooperation with beauty influencers who have a strong influence in order to increase purchasing decisions on digital platforms such as TikTok. Keywords: Online Customer Review, Beauty Influencers, Purchase Decision